Nephrite placers types of Kunlun and adjacent Tarim depression, China - P. A. Ignatov; Chjao Hen (Известия высших учебных заведений: Геология и разведка, 2015)
Preconditions of nephrite placers formation in the Central Kunlun mountains and adjacent Tarim depression are considered in Russian literature for the first time: the presence of the primary deposits in metasomatic rocks localized in alpine-type ultramafic and contact-metasomatic rocks; optimal erosional truncation and hydrodynamic trap sites of valuable minerals accumulation; contrast neotectonics; variable climate conditions. The types of nephrite placers have been distinguished: deluvium (boulder stream), morainic valley deposits, proluvial, alluvial of mountain and plain rivers, surface deltas. The examples of typical landscapes of placers are given. Surface delta placers appeared to be modern and ancient buried. The residual placers resources of different genetic types are poor except surface deltas placer. It is justified that the surface deltas (delta fan) deposits in the studied region may contain nephrite placers.